2019
DOI: 10.1016/j.seizure.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Women with epilepsy in sub–Saharan Africa: A review of the reproductive health challenges and perspectives for management

Abstract: Background: Epilepsy is one of the commonest neurological conditions affecting women of reproductive age. Epilepsy management during pregnancy is a clinical conundrum, requiring a balance between seizure control and risk minimization for the women with epilepsy (WWE) as well as for their fetuses. The objective of this comprehensive review is to explore the reproductive health challenges of WWE in sub-Saharan Africa (SSA) and ways to address them. Method: Relevant documentation published until June 2019 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Phenobarbital, as all first line AED available in sub-Saharan Africa, has been associated with congenital abnormalities [30]. Therefore, more advocacy is needed to make safer second line AED [31,32] available at an affordable price.…”
Section: Discussionmentioning
confidence: 99%
“…Phenobarbital, as all first line AED available in sub-Saharan Africa, has been associated with congenital abnormalities [30]. Therefore, more advocacy is needed to make safer second line AED [31,32] available at an affordable price.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 43% of our cohort used VPA in their polytherapy regimen, but with no increase in the risk of major fetal malformations. Current guidelines strongly discourage such approach [19][20][21] . Our findings suggest the higher rate of major fetal malformations in VPA monotherapy group to be dose-related, with no evidence for preconception folate supplementation to reduce that risk.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to AED during pregnancy is associated with an increased risk of preterm birth ( 20 ). Furthermore, our study recorded such association and found a significantly increased risk of preterm birth in polytherapy group compared to monotherapy group (p=0.03).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the geographic overlap with other endemic diseases, a non-negligible proportion of pregnant HIV+ WWE may concomitantly receive treatment with other potentially teratogenic drugs, including anti-TB drugs [32]. Therefore, epilepsy management during pregnancy, particularly in HIV+ women, requires an equilibrium between seizure control, viral load control, co-infection prevention, and risk minimization for the WWE and their fetuses [33].…”
Section: Introductionmentioning
confidence: 99%